Sodium bicarbonate - Williams, A.
Bicarbonate has been researched by sports scientists for some time, producing inconsistent results, though some studies have suggested it has great potential for enhancing anaerobic performance. Perhaps the one major confounding factor is the relatively common side-effect of stomach problems.